Cationic Vacancy Defects in Iron Phosphide: A Promising Route toward Efficient and Stable Hydrogen Evolution by Electrochemical Water Splitting. Issue 22 (27th October 2017) - Kwong, Wai Ling; Gracia‐Espino, Eduardo; Lee, Cheng Choo; Sandström, Robin; Wågberg, Thomas; Messinger, Johannes
Abstract: Engineering the electronic properties of transition metal phosphides has shown great effectiveness in improving their intrinsic catalytic activity for the hydrogen evolution reaction (HER) in water splitting applications. Herein, we report for the first time, the creation of Fe vacancies as an approach to modulate the electronic structure of iron phosphide (FeP). The Fe vacancies were produced by chemical leaching of Mg that was introduced into FeP as "sacrificial dopant". The obtained Fevacancy‐rich FeP nanoparticulate films, which were deposited on Ti foil, show excellent HER activity compared to pristine FeP and Mg‐doped FeP, achieving a current density of 10 mA cm −2 at overpotentials of 108 mV in 1 m KOH and 65 mV in 0.5 m H2 SO4, with a near‐100 % Faradaic efficiency. Our theoretical and experimental analyses reveal that the improved HER activity originates from the presence of Fe vacancies, which lead to a synergistic modulation of the structural and electronic properties that result in a near‐optimal hydrogen adsorption free energy and enhanced proton trapping. The success in catalytic improvement through the introduction of cationic vacancy defects has not only demonstrated the potential of Fe‐vacancy‐rich FeP as highly efficient, earth abundant HER catalyst, but also opens up an exciting pathway for activating other promising catalysts for electrochemical water splitting. Abstract : When less is more : Fe‐vacancy‐rich FeP, prepared by chemical leaching of Mg that is introduced into FeP as sacrificial dopant, exhibits superior electrocatalytic activity for hydrogen evolution reaction compared to pristine FeP and Mg‐doped FeP. The presence of cationic vacancy defects modulates the structural and electronic structures of FeP, thereby resulting in enhanced proton trapping and surface interaction with adsorbed hydrogen atoms.